SORONG FAULT KINEMATICS AS AN IMPLICATION FOR STRUCTURAL EVOLUTION ON SERAM, MISOOL, AND SALAWATI BASIN - RIADINI, PUTRI
The main research objective is the evolution of Sorong Fault Zone (SFZ) in the Bird’s Head region of Papua as implication of the evolution of Salawati Basin, Misool-Onin-Kumawa Anticline (MOKA), and Seram Fold-Thrust Belt (SFTB). The SFZ is a left-lateral fault system located in the northern margin of Papua extended thousands kilometers from the Eastern part of the island to the Bird's Head region. SFZ is an active fault system starting on the Late Miocene. Our new model indicates that SFZ rotates the Bird's Head area, including Salawati Basin to the west. The movement of SFZ involves rotation and translation that separates Salawati Basin from the Bird's Head region with basement high as the boundary of the basin. More than 100 seismic lines have been interpreted along Seram, Misool, and Salawati offshores. These interpretations show the development of listric and planar normal faulting at western part of Misool Island and pop-up structure at NW Bird's Head region. The evidence was interpretated as a result of SFZ activities, which cut Paleozoic through the Tertiary formations. The listric and planar normal fault mechanism in the Salawati basin explains that the rifting event connected to Bird's Head rotation. In addition, flower structures observed at NW Bird’s Head indicate the shortening effect that also associated with the SFZ activities. Seemingly, rotation and translation of SFZ to the west are associated with the evolution of SFTB that indicate by NE-SW shortening perpendicular to the island. The deformation in the SFTB is involved Pliocene sediments. Therefore, SW directed shortening as a response of counter clockwise rotation of the Bird Head region with additional westward movement of Tarera-Aiduna strike-slip system to the west forms SFTB. New seismic interpretation combined with palinspatic reconstructions suggests that there are rotation and translation phase in relation to SFZ mechanism that develops the Salawati Basin, MOKA, and SFTB. These deformations mechanism are active since the Late Miocene related to the collision between Pacific island arc complexes and passive margin of NW Australian plate.